Evolution of Sacred Traditions: The Inclusive Transformation of the Besale Ritual among the Suku Anak Dalam, Indonesia - Asniah, Asniah; Ahmad, Sulthan; Wahyuni, Dwi (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This research investigates changes in the Besale ritual tradition, a ceremony aimed at cleansing the soul tainted by malevolent spirits. Initially conducted privately and exclusively for the Suku Anak Dalam, the Besale ritual has now become an open event in the Dwi Karya Bhakti Village, even accessible to the general public. This study employs a qualitative descriptive method, collecting data through observation, interviews, and documentation, and analyzing it using the Creswell model. The research findings reveal five main patterns of change in the Besale ritual tradition, involving shifts in the value system, cognitive system, interaction system, institutional system, and behavioral acceptance level. These changes did not occur spontaneously but rather through an interactive process involving various social groups within the Suku Anak Dalam. The results of this study provide valuable insights into the dynamics of cultural and traditional changes in society, shedding light on how social factors and intergroup interactions can influence cultural transformations. These findings can serve as a valuable resource for cultural preservation efforts in various evolving societal contexts.